Reduction in Regulatory T Cells in Early Pregnancy Causes Uterine Artery Dysfunction in Mice. Issue 1 (July 2018) - Care, Alison S.; Bourque, Stephane L.; Morton, Jude S.; Hjartarson, Emma P.; Robertson, Sarah A.; Davidge, Sandra T.
Abstract : Preeclampsia, fetal growth restriction, and miscarriage remain important causes of maternal and perinatal morbidity and mortality. These complications are associated with reduced numbers of a specialized T lymphocyte subset called regulatory T cells (Treg cells) in the maternal circulation, decidua, and placenta. Treg cells suppress inflammation and prevent maternal immunity toward the fetus, which expresses foreign paternal alloantigens. Treg cells are demonstrated to contribute to vascular homeostasis, but whether Treg cells influence the vascular adaptations essential for a healthy pregnancy is unknown. Thus, using a mouse model of Treg-cell depletion, we investigated the hypothesis that depletion of Treg cells would cause increased inflammation and aberrant uterine artery function. Here, we show that Treg-cell depletion resulted in increased embryo resorption and increased production of proinflammatory cytokines. Mean arterial pressure exhibited greater modulation by NO in Treg cell-deficient mice because the L-N G -nitroarginine methyl ester–induced increase in mean arterial pressure was 46% greater compared with Treg cell-replete mice. Uterine artery function, which is essential for the supply of nutrients to the placenta and fetus, demonstrated dysregulated hemodynamics after Treg-cell depletion. This was evidenced by increased uterine artery resistance and pulsatility indices and enhanced conversion of bET-1 (big endothelin-1) to the active and potent vasoconstrictor, ET-1 (endothelin-1). These data demonstrate an essential role for Treg cells in modulating uterine artery function during pregnancy and implicate Treg-cell control of maternal vascular function as a key mechanism underlying normal fetal and placental development. Abstract : Supplemental Digital Content is available in the text.